Green Marketing And Climate Change: The Case Of Starbucks Indonesia - Fauzil Azmi; Ali Maksum (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
This journal examines the contribution of the Starbucks company to environmentally friendly issues that have an impact on climate change, especially Starbucks Indonesia. This journal aims to describe and analyze why and to what extent Starbucks Indonesia contributes to environmentally friendly issues. As we all know, climate change is a big challenge for Indonesia and the world. Starting from temperature changes, changes in rainfall patterns, drought and lack of clean water, extreme weather changes, to rising sea levels, climate change occurs due to increasing concentrations of greenhouse gases in the atmosphere such as carbon dioxide (CO2), methane (CH4), and nitrogen oxides (N2O). To complete the data, this research will be enriched with primary data in the form of interviews and field observations at a Starbucks Indonesia company and use library research data collection techniques by utilizing secondary data collected from libraries, books, journals, articles, print media, electronic media, and websites. The descriptive-analytical approach was used to collect and analyze the data. The analysis of this research uses green theory and green marketing to find out why and to what extent Starbucks Indonesia's contribution contributes to environmentally friendly issues. Environmental issues are issues all over the world that often arise. Governments, organizations, and some groups have been actively holding business companies to account regarding environmental damage such as unusual climate change, global warming, natural resource degradation, and population. In this case, the aim is for consumers to have significant environmental awareness and become more concerned with green products and contribute to a green environment.